2020
DOI: 10.18510/hssr.2020.8185
|View full text |Cite
|
Sign up to set email alerts
|

Assertiveness Predicts Self-Esteem, Academic Achievement, and Stress: A Study of Kashmiri Adolescents

Abstract: Purpose of the study: The adolescence period holds a special significance because this period marks multi-developmental changes in an individual. The present study was conducted to find out the association between assertiveness, self-esteem, academic achievement and stress among the students. Methodology: Correlational design was employed for the present research. Participants of the study comprised 120 high school students with an equal number of male and female students and the age range of 12 to 19 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The current study has been confirmed by Khansa Malik and Bince Varghese [ 10 ], who conducted a study on the impact of assertiveness training on adolescents' self-esteem in 2020. Our results were also in agreement with Parry (2017) [ 5 ]. An Indian Outlook found that the training had a positive impact on adolescents' self-esteem.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study has been confirmed by Khansa Malik and Bince Varghese [ 10 ], who conducted a study on the impact of assertiveness training on adolescents' self-esteem in 2020. Our results were also in agreement with Parry (2017) [ 5 ]. An Indian Outlook found that the training had a positive impact on adolescents' self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…According to a study, self-esteem and academic success are two aspects that assertiveness does not significantly influence. The researcher also discovered that 13%-15% of adolescents in India exhibited passive behaviour [ 5 ]. In The location of Mehsana, 25% to 27% of adolescents had been influenced by low levels of assertive behaviour, and 47% to 49 percent of adolescents in Gujarat exhibited low levels of this behaviour [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…41 Additionally, as the concept of self-embodies a perception that was embedded since the childhood period, the initiatives to change it need a long time. 29 Besides, trying to adapt to new rules and changes and feeling anxiety, hopelessness and academic uncertainty due to the pandemic 42 might have made this change hard for both the experimental and control groups. In a study, it was found that there was a positive relationship between academic achievement and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that assertive behavior is the assimilation of specific cognitive patterns of interaction that can accumulate and promote social integration (2016). R. Maqbool investigated the relationship between assertiveness, self-esteem, academic achievement, and stress (Maqbool Parray et al, 2020). Khodabakhshi-Koolaee A. and coauthors found the influence of emotional intelligence on the development of assertiveness and self-esteem (2016).…”
Section: The Concept Of Personality Assertiveness In Researchmentioning
confidence: 99%